Percepção de estudantes de enfermagem na prática deliberada em ciclos rápidos e no treinamento de habilidades para cenário de suporte básico de vida - Sudan, Leticia (2025)
Clinical simulation is an effective strategy for health training, as it aims to reduce the gap between theory and practice. Nursing students, as future professionals, need to maintain well-consolidated theoretical and practical knowledge to intervene immediately in emergency situations. Objective: To analyze the experience of nursing students in Deliberate Practice in Rapid Cycles and in skills training followed by a Simulated Scenario for Basic Life Support. Method: This is a qualitative study of the descriptive-exploratory type, guided by the Consolidated Criteria for Reporting Qualitative Research (COREQ) guide. The study was developed at the Health Simulation Unit (USS) of the Federal University of São Carlos (UFSCar), located in the city of São Carlos. The sample consisted of 12 students included based on the following criteria: being regularly enrolled in the Undergraduate Nursing Course at the Federal University of São Carlos and being over 18 years old. Students who had any training on BLS content using AED during their professional training process with the PDCR technique, skills training associated with high-fidelity simulation, were excluded from the study. All were invited to voluntarily participate in the research during the period from September to November 2025. Data collection took place through semi-structured interviews based on a Holistic Debriefing guide that were conducted by two trained researchers, after training in Basic Life Support (BLS) with Rapid Cycle Deliberate Practice (RCP) or with Simulated Skills Training. The interviews were audio-recorded and transcribed in full, and the data were analyzed using the Clark and Brown Analysis technique. Results: From the analyzed data, three empirical categories emerged: 1) Students' perceptions in relation to the different simulated practices; 2) Contributions in relation to the development of technical and non-technical skills; 3) Feelings before, during and after the simulation. The students were satisfied with the simulation techniques, especially when compared to traditional teaching methods. They emphasized the importance of repetitions and feedback from the RCDP, as well as working in a safe and realistic environment during the Simulated Scenario. Conclusion: The evaluation of the experience of nursing students with Rapid Cycle Deliberate Practice (RCDP) and Skills Training, followed by the simulated scenario during Basic Life Support (BLS), highlighted the relevance of implementing active teaching methodologies in nursing training. The use of simulation methods proved to be effective, promoting significant gains such as increased self-confidence, leadership and the ability of students to deal with intense emotions such as anxiety and stress. In addition, the importance of conducting new studies that investigate the experiences of nursing students with simulation techniques in health education is highlighted, as these studies are essential to identify the need for adaptations in the traditional teaching method.